Constraints in Convergence for Dairy Development: A System’s Analysis - V B Dixit , Hema Tripathi , S Singh; I Singh (Indian Journal of Extension Education, 2018)
The study was conducted in Haryana - the state of India which is well known for its bovine wealth. The study was conducted to identify constraints in convergence of different agencies working for dairy development. The respondents constituted 50 animal scientists working in state veterinary university and research institutes of Indian Council of Agricultural Research (ICAR) representing disciplines like extension, Livestock Production and Management( LPM) animal nutrition, reproduction ,medicine, etc. Also 50 field functionaries working in Hisar district of Haryana state were the respondents for the study .Out of which there was randomly selected 30 field veterinarians and 20 senior officials working in ATMA, dairy cooperatives, lead banks, DRDA, input agencies and NGOs. After a thorough editing, 31 constraints in convergence of different agencies working for dairy development emanating from interaction with them were identified for eliciting the response on 5 point continuum. Thus serious and comparatively less serious constraints were identified by subjecting the data to k-means cluster analysis. The constraints in convergence so identified were classified into different groups. The analysis grouped 31 items into 5 clusters and each included 10 administrative, 11 functional, 6 operational 2 organizational and 2 policy related constraints. The study further endeavored to identify serious and comparatively less serious constraints in convergence of different agencies for dairy development.